Essence, Development And Role Of Representative Authority In The Development Of Society (Eurasian Journal of Learning and Academic Teaching, 2021)
The scientific article analyzes the processes of formation and development of representative power, views on it, scientific conclusions and their differences. It also discusses the power of state power and its role in society. There is talk about the essence of representative bodies and civil society institutions, their impact on the development of society. The role and place of the development of cooperation between the representative government and civil society institutions in the development of society will be analyzed